USE OF PHYSICAL FACTORS IN MEDICINE (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
The development of science and technology, industry and scientific research cannot be imagined without physical factors. Physical factors are widely used, especially in many areas of medicine. This is especially noticeable in diagnostics, treatment, surgical intervention and laboratory studies of various diseases. The movement of blood through the vessels in a living organism is also assessed by physical factors. This article explains the movement of blood through the vessels using some physical factors.